(untitled) (Heritage, 2021)
This paper discusses theoretical frameworks and models that focus on technology, ethodological, motivational and pedagogical aspects of online education. After reviewing the theory of learning in the context of online education, with the proposal of an integrative model of approach to emerging challenges. This paper discusses theoretical frameworks and models that focus on technological, methodological, motivational, and pedagogical aspects of online education. After discussing the theory of learning and the technological context of online education, authors have provided an overview of interactive modalities that have the potential to meet the requirements the future development of technology puts before education.